The Historical Study of Castles in Oman (Jalali) as a Model - Odah, Bushra Kadhim (Opción, 2019)
The aim of the study is to investigate the historical study of castles in Oman (Jalali) as a model via comparative qualitative research methods. As a result, the castle became a center of attraction and attention to local, regional or international powers, and then developed in the era of AL- Boussaid, and became an administrative center and later transformed as a central prison for Oman. In conclusion, the form of castle differs from the time it had before, by virtue of the reforms and renovations carried out by the Portuguese rule until the modern Renaissance in Oman.